2013
DOI: 10.1186/gb-2013-14-2-r17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the core and accessory genomes of 48 Sinorhizobium strains comprising five genospecies

Abstract: BackgroundThe sinorhizobia are amongst the most well studied members of nitrogen-fixing root nodule bacteria and contribute substantial amounts of fixed nitrogen to the biosphere. While the alfalfa symbiont Sinorhizobium meliloti RM 1021 was one of the first rhizobial strains to be completely sequenced, little information is available about the genomes of this large and diverse species group.ResultsHere we report the draft assembly and annotation of 48 strains of Sinorhizobium comprising five genospecies. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
123
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 50 publications
(66 reference statements)
16
123
1
Order By: Relevance
“…2A). Similar to the findings of previous studies that conducted pangenome analyses (43,45,49), the highest number of core genes was observed in the functional category J (translation, ribosomal structure, and biogenesis). Furthermore, functional assignment based on COG classification revealed that most FIG 2 Pangenome analysis of Sulfobacillus strains.…”
Section: Figsupporting
confidence: 88%
See 1 more Smart Citation
“…2A). Similar to the findings of previous studies that conducted pangenome analyses (43,45,49), the highest number of core genes was observed in the functional category J (translation, ribosomal structure, and biogenesis). Furthermore, functional assignment based on COG classification revealed that most FIG 2 Pangenome analysis of Sulfobacillus strains.…”
Section: Figsupporting
confidence: 88%
“…S. thermosulfidooxidans Cutipay had the largest genome size (3.86 Mb) and number of CDSs (4,250), whereas S. thermosulfidooxidans DX had the smallest genome size (3.18 Mb) and number of CDSs (3,211). These findings indicated that numerous accessory genes in S. thermosulfidooxidans Cutipay were likely acquired by HGT, similar to earlier comparative genomic analyses of Sinorhizobium strains (45,46).…”
Section: Figsupporting
confidence: 84%
“…syrM, nodD3, and syrA appear to be universal in the Sinorhizobium genus based on published genome sequences (95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Among S. meliloti and S. medicae strains, the orthologous proteins are nearly identical, and the gene arrangement is syntenic to S. meliloti Rm1021 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rm1021 lacks functional genes encoding NolR, a nod gene repressor (109), ExpR, an LuxR-family global regulator of population-based behavior (6), EcfRI, which regulates sulfite metabolism (110), PstC, involved in high-affinity phosphate transport (111), and perhaps others (99,102). NolR of S. meliloti Rm41 represses expression of nodD1 and nodD2 but probably not nodD3 and syrM (112); NolR may also regulate genes involved in bacterial growth, survival, and conjugative plasmid transfer (113).…”
Section: Discussionmentioning
confidence: 99%
“…viciae population. This core value is similar in size to genetic cores found for other related species, such as Ensifer medicae (5,036 core genes for 12 genomes), E. fredii (5,979 core genes for 2 genomes) or E. meliloti (4,680 core genes for 32 genomes) (Sugawara et al, 2013). …”
Section: Exclusive Genes In Plant Host Mesocosm-selected Strainssupporting
confidence: 81%